Introduction to the Perturbation Theory of Hamiltonian Systems - Treschev, Dmitry; Zubelevich, Oleg (Springer Monographs in Mathematics, 2010)
This book presents the basic methods of regular perturbation theory of Hamiltonian systems, including KAM-theory, splitting of asymptotic manifolds, the separatrix map, averaging, anti-integrable limit, etc. in a readable way. Although concise, it discusses all main aspects of the basic modern theory of perturbed Hamiltonian systems and most results are given with complete proofs. It will be a valuable reference for Hamiltonian systems, and of special interest to researchers and graduate students of the KAM community.